Comparative and Legal Analysis of the Legal Entities System of Ukraine and the European Union - ZOZULYAK, Olga I.; KOVALYSHYN, Oleksandr R.; GRYSHKO, Uliana P. (Journal of Advanced Research in Law and Economics; Vol 9 No 8 (2018): JARLE Volume IX Issue 8(38) Winter 2018DO - 10.14505//jarle.v9.8(38).42, 2019)
Issues of the system and legal status of legal entities are traditionally widely covered in domestic civilization; however, there was no comparative legal analysis of the system of legal entities of Ukraine and the European Union. According to the results of the study, it was stated that the system of legal entities, in terms of its legislative design, is a holistic legal institution, the norms of which mediate the creation and participation in civilian turnover of legal entities as independent subjects of law. The analysis of doctrinal approaches to the definition of ‘system of legal entities’ allowed proposing an author's definition of the concept, which suggests understanding the orderly set of organizations with the status of a legal entity, integrated into the complex of interacting elements according to certain criteria. On the basis of a detailed study of the peculiarities of the system of legal entities of the European Union, the definition of the concept of ‘system of legal entities of the European Union’ is formulated.